Mr. & Mrs. J. Acklen with their two children, Charlotte and Joe, on the front porch of their home, Dawson, Yukon Territory, ca. 1901. - University of Washington Libraries. Special Collections Division
PH Coll 246.270 Mrs. Acklen was a school teacher. [Meed journal: "Mr & Mrs. J. Acklen with their 2 children Charlotte and Joe on the front porch of their home."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number